Serum Copper and Zinc Levels and Risk of Hepatocellular Carcinoma: A 1:1 Matched Case-Control Study. (29th May 2020) - Fang, Aiping; Zhu, Huilian
Abstract: Objectives: Copper and zinc have been involved in the development of liver cancer in laboratory models, yet data from epidemiological studies are limited. We investigated the association of serum levels of copper and zinc and their ratio with the risk of hepatocellular carcinoma (HCC) in a Chinese population. Methods: This is a 1:1 matched case-control study conducted between September 2013 and February 2017. Each case with newly diagnosed HCC from the Guangdong Liver Cancer Cohort (GLCC) was matched to one healthy control from the Guangzhou Nutrition and Health Study by age (±1 years) and sex. Serum copper and zinc levels were quantified using inductively coupled plasma mass spectrometry. Conditional logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) adjusted for age, sex, body mass index, hepatitis infection, smoking status, alcohol drinking status, diabetes, and chronic inflammation. Serum levels of copper and zinc and their ratio were included in models in tertiles with cutpoints based on the distribution of the control participants. Results: A total of 556 case-control pairs were included in this study. Mean (SD) age was 60.3 (7.1) years and 83.8% of the participants were men. HCC cases had significantly higher copper and lower zinc levels, and thus higher copper/zinc, than controls. Higher serum zinc levels were associated with a lower risk of HCC (ORT3 vs T1  = 0.21; 95% CI: 0.07–0.64, P for trend = 0.005). However, there was no association between serum copper levels and HCC risk (ORT3 vs T1  = 1.53; 95% CI: 0.62–3.76, P for trend = 0.375). Higher copper/zinc ratio was associated with increased risk of HCC (ORT3 vs T1  = 3.06; 95% CI: 1.08–8.70, P for trend = 0.049). Conclusions: Serum zinc levels were inversely associated with the risk of HCC, suggesting a protective role of zinc in preventing HCC development. Funding Sources: This work was supported by the National Natural Science Foundation of China.